Biochemical conversion of sugarcane bagasse into bioproducts. (October 2016) - Jain, Arpan; Wei, Yanzhang; Tietje, Ashlee
Abstract: The ground sugarcane bagasse conversions were examined through chemical treatment methods employing soaking in aqueous ammonia (SAA), and ethyl-hydro-oxides (EHOs). To characterize a chemical treatment method, both generated solvent based extract and pulp were examined. The generated pulps were evaluated through chemical composition and enzymatic saccharification. The enzyme mixtures were investigated including Trichoderma reesei Rut C-30 originated cellulase, T. reesei Rut C-30 originated cellulase with external added β-glucosidase, Accellerase ® 1500, and Cellic ® CTec2. The physiochemical effects of chemical treatments on the structural-chemical properties of treated-bagasse were also analyzed at high substrate enzymatic saccharification. The substrate loadings (using both SAA-treated and EHOs-treated bagasse) of 125, 150, 175, 200, and 225 g L −1 were examined during enzymatic saccharification process. The generated phenolic compounds were characterized based on density, antioxidant activity, and anticancer activity. All findings are discussed in relation to developing a self-sustainable integrated biorefinery. Highlights: A comparative analysis of sugarcane bagasse conversion using SAA and EHOs treatments. Enzyme hydrolysis at high substrate loadings using different enzyme preparations. The development of pharmaceutical product using a lignin fraction. The process of developing a self-sustainable integrated biorefinery.